Management of occupational hazards in healthcare: exposure to diphencyprone. (15th February 2013) - Basu, Subhashis; Adisesh, Anil
Abstract : Diphencyprone is a chemical agent used most commonly in the treatment of alopecia areata. Its mechanism of action is through the sensitisation (type IV immune reaction) of affected areas to stimulate hair follicle growth. The consequences of accidental occupational exposure, however, have not been widely recognised. This report describes the clinical presentation and management of two pharmacy technicians that presented to Sheffield Occupational Health Service (SOHS) centre in 2012. Exposure sources were identified through a workplace visit arranged between the SOHS centre and the hospital's pharmacy; a chemical analysis revealed concentrations of the chemical sufficient to induce sensitisation at several points during the manufacturing process. The case highlights the role of close liaison between specialist services (dermatology and occupational medicine) in managing individual patient cases and mitigating risk within relevant occupational groups.